Thrombin Hemostatic Matrix Reduces Heterotopic Ossification in Acetabular Fractures Fixed Through the Kocher–Langenbeck Approach. Issue 9 (September 2020) - Montgomery, Tyler; Pearson, Jeffery; Agarwal, Abhinav; Olinger, Catherine; Tobey, Devon; Beebe, Michael; McGwin, Gerald; Cichos, Kyle; Ghanem, Ellie; Spitler, Clay; Dubose, Candace; Quade, Jonathan
Abstract : Objective: To determine whether an injectable thrombin product [thrombin hemostatic matrix (THM)] at closure of a Kocher–Langenbeck approach reduces the risk of heterotopic ossification (HO) formation after an acetabular fracture. Design: Case control. Setting: Two Level 1 trauma centers. Patients: Patients with operatively treated acetabulum fractures fixed through Kocher–Langenbeck from 2013 to 2018. Intervention: Records were reviewed for demographics, history of traumatic brain injury, HO medication or radiation prophylaxis, THM (Surgiflo, Ethicon, Bridgewater New Jersey) administration, and length of follow-up. Radiographs were reviewed for dislocation, fracture, Letournel and Orthopaedic Trauma Association classifications, HO, and Brooker grade if applicable. Patients receiving HO prophylaxis (eg, nonsteroidal anti-inflammatory drugs and radiation) were excluded. Remaining patients were divided into 2 groups: THM administration (intervention) and no THM. Continuous variables were compared using t -tests and categorical variables with chi-square or Fisher's exact tests. Main Outcome Measurements: Risk ratios for the association between HO occurrence and THM administration. Results: Three-hundred and twenty-eight acetabular fractures met inclusion criteria (126 intervention, 202 control) in patients with a mean age of 38.7 ± 15.9 years; 62.2% were male, and 42.1% were African American. Traumatic brain injury and posterior dislocation rates were equivalent between groups ( P = 0.505, 0.754, respectively). HO rate in the control group was 42.6% compared with 21.4% in the THM group ( P < 0.001). Booker grade 3/4 in control group was 17.3% versus 3.2% in the THM group ( P < 0.001). Patients receiving THM had a 50% reduced risk of HO (95% confidence interval 0.35–0.73) compared to those who did not; adjustment for age, gender, ethnicity, and traumatic brain injury did not meaningfully change the association (risk ratio 0.46; 95% confidence interval 0.29–0.73; P < 0.001). Conclusion: The use of a surgiflo product at closure of a KO approach may reduce the risk of HO formation by 50% after an acetabular fracture. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.